2009
DOI: 10.1017/s1366728909004027
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual children's sensitivity to specificity and genericity: Evidence from metalinguistic awareness

Abstract: A number of recent studies have argued that bilingual children's language comprehension and production may be affected by cross-linguistic influence. The overall aim of this study was to investigate whether the ability to judge the grammaticality of a construction in one language is affected by knowledge of the corresponding construction in the other language. We investigated how English–Italian and Spanish–Italian bilingual children and monolingual peers judged the grammaticality of plural NPs in specific and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 39 publications
9
116
3
2
Order By: Relevance
“…production of definite before indefinite articles; no equal distribution of definite and indefinite articles by 2;6 (see Prévost, 2009 Unlike in previous corpus studies of determiner development (Kupisch, 2003;, we report a small number of instances of cross-linguistic transfers. As in experiments with older bilinguals (Serratrice et al, 2009;Kupisch & Pierantozzi, 2010), these instances occurred from the Germanic language, i.e. English, to the Romance language, i.e.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…production of definite before indefinite articles; no equal distribution of definite and indefinite articles by 2;6 (see Prévost, 2009 Unlike in previous corpus studies of determiner development (Kupisch, 2003;, we report a small number of instances of cross-linguistic transfers. As in experiments with older bilinguals (Serratrice et al, 2009;Kupisch & Pierantozzi, 2010), these instances occurred from the Germanic language, i.e. English, to the Romance language, i.e.…”
Section: Discussionmentioning
confidence: 64%
“…On the contrary, if language exposure plays a role on the magnitude of CLI (Serratrice, et al 2009), then comparable direction and amplitude of CLI should be observed given our bilinguals' comparable exposure to French and English.…”
Section: Research Questions and Predictionsmentioning
confidence: 72%
See 2 more Smart Citations
“…Much research on the morphosyntax-semantics mapping has been done in the aspectual domain. In the nominal realm, bilingual/second language acquisition research has mostly focused on the semantics of the article system (Ionin et al 2004;Goad & White 2004;Trenkic 2007;Ionin et al 2008) and the grammaticality of plural noun phrases in different semantic contexts (Serratrice et al 2009). For instance, Ionin et al (2004) found that when speakers from article-less languages (e.g., Russian and Korean) learn a language with an article system (e.g., English), they do not necessarily map the article to the correct meaning of definiteness, but rather fluctuate between the meanings of definiteness and specificity.…”
Section: Introductionmentioning
confidence: 99%